Circulating small extracellular vesicles from patients with periodontitis contribute to development of insulin resistance. Issue 12 (24th July 2022) - Wang, Fei; Peng, Linlin; Gu, Fan; Huang, Pei; Cheng, Bo; Chen, Gang; Meng, Liuyan; Bian, Zhuan
Abstract: Background: Epidemiological studies have identified the role of periodontitis in the pathogenesis of type 2 diabetes, but the underlying mechanism is poorly understood. It is well‐known that small extracellular vesicles are lipid bilayer vesicles derived from cells with a diameter around 30 to 200 nm. The purpose of this study was to investigate whether periodontitis induced or exacerbated insulin resistance via circulating small extracellular vesicles. Methods: Plasma small extracellular vesicles from control and periodontitis rats were intravenously injected into type 2 diabetic rats. Insulin tolerance tests, glucose tolerance tests, and the activation of the insulin signaling pathway were measured to detect the effect of the plasma small extracellular vesicles on insulin sensitivity. In addition, circulating small extracellular vesicles from patients with periodontitis with or without diabetes were isolated and co‐cultured with HepG2 cells. The ability of glucose uptake was assessed using the fluorescence of 2‐NBDG via flow cytometry. The activation of insulin signaling pathway was examined via Western blotting. Real time quantitative polymerase chain reaction (RT‐qPCR) was used to detect the expression of enzyme related to glycolysis and gluconeogenesis. Results: Small extracellular vesicles derived from the plasma of periodontitis rats further impaired glucose tolerance and insulin tolerance in diabetic rats and significantly reduced the activation of the insulin signaling pathway in liver tissues, as evidenced by the decreased levels of p‐AKT and p‐GSK3β and the reduced hepatic glycogen content. For small extracellular vesicles isolated from human plasma, the concentration of small extracellular vesicles in patients with type 2 diabetes combined with periodontitis was higher than that of the healthy control and periodontitis alone. Moreover, circulating small extracellular vesicles from patients with periodontitis significantly inhibited the glucose uptake capacity and inhibited insulin signaling of HepG2 cells. Conclusion: Periodontitis acted as a contributing factor to exacerbate insulin resistance of type 2 diabetic rats. Plasma small extracellular vesicles played a critical role in periodontitis aggravating insulin resistance.